2018
DOI: 10.1038/s41598-018-21166-7
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the homeostatic protein BPIFA1, leads to exacerbation of otitis media severity in the Junbo mouse model

Abstract: Otitis Media (OM) is characterized by epithelial abnormalities and defects in innate immunity in the middle ear (ME). Although, BPIFA1, a member of the BPI fold containing family of putative innate defence proteins is abundantly expressed by the ME epithelium and SNPs in Bpifa1 have been associated with OM susceptibility, its role in the ME is not well characterized. We investigated the role of BPIFA1 in protection of the ME and the development of OM using murine models. Loss of Bpifa1 did not lead to OM devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 50 publications
(69 reference statements)
0
14
0
Order By: Relevance
“…Bpifa1 (also known as Splunc1) is one of the most abundant secretory proteins in the upper respiratory tract (Musa et al, 2012; Mulay et al, 2016, 2018) and the mesenchyme border has an intense Bpifa1 in situ hybridization (ISH) signal (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Bpifa1 (also known as Splunc1) is one of the most abundant secretory proteins in the upper respiratory tract (Musa et al, 2012; Mulay et al, 2016, 2018) and the mesenchyme border has an intense Bpifa1 in situ hybridization (ISH) signal (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that the Junbo -/+ OM mouse, which is heterozygous for a mutation in Mecom/Evi1 [32]. develops an exacerbated OM phenotype when Bpifa1 is also removed [4]. In addition, the ALI cells also exhibit some expression if some known human OM susceptibility genes.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of three well validate human OM associated genes Fndc1 [27], Fut2 [28] and A2ml1 (BC048546) [29] was detected in the mMMECs with the highest expression being for BC048546 in the day 7 differentiated cells ( Figure 2F). Expression of four OM associated genes identified through ENU mutagenesis screening: Tgif1 [30], Fxbxo11 [31], Mecom [32] and Nisch [33} is clearly seen in both the undifferentiated and differentiated cells, with Mecom (Evi1) the gene mutated in the Junbo +/-OM mouse model [4,32] being most differentially expressed during differentiation. The expression of a further, representative group of genes associated with murine OM was shown to be variable with Oxgr1 [34] being essentially not expressed in the cells whereas Rpl38 [35] was the most highly expressed.…”
Section: Expression Of Om Associated Genes In the In Vitro Mouse Middmentioning
confidence: 99%
See 1 more Smart Citation
“…Later studies have shown that the loss of BPIFA1, one of the most abundant secretory proteins in the upper respiratory tract (Musa et al, 2012), exacerbates the severity of OM in Junbo mice. While Bpifa1 mutant mice did not show any OM susceptibility, the deletion of Bpifa1 in mice carrying Evi1 Junbo variant leads to the thickening of the middle ear mucosa and an increase of collagen deposition (Mulay et al, 2018). Loss of Tgif1, which encodes for TGIF1, results in OME accompanied by the thickening of the middle ear epithelial lining, an increase of goblet cell population, elevated levels of TNFα and IL-1β in ear fluids, and conductive hearing loss in mice (Tateossian et al, 2013).…”
Section: Mouse and Mouse-to-man Studiesmentioning
confidence: 94%